Geología de los cuadrángulos de Jayanca (13-d), Incahuasi (13-e), Cutervo (13-f), Chiclayo (14-d), Chongoyape (14-e), Chota (14-f), Celendín (14-g), Pacasmayo (15-d), Chepén (15-e) - [Boletín A 38] - Wilson, John J. (1984)
104 p.